Retracted: Primary Percutaneous Coronary Intervention (PPCI) in Acute Myocardial Infarction Complicated by Cardiogenic Shock in a Newly Emerging Cardiac Centre in Nepal - Maskey, Arun; Regmi, Shyam Raj; Bhatt, Yadav; Malla, Rabi; Rajbhandari, Rajib; Sharma, Deewakar; KC, Man Bahadur; Limbu, Yuba Raj; Dubey, Laxman (Nepalese Heart Journal, 2017)
The following retraction notice for this article appears in Vol.16(1) 2019 DOI: https://doi.org/10.3126/njh.v16i1.25742 On 17th September 2019 the Editorial Board of Nepalese Heart Journal agreed to retract the article ‘Primary Percutaneous Coronary Intervention (PPCI) in Acute Myocardial Infarction Complicated by Cardiogenic Shock in a Newly Emerging Cardiac Centre in Nepal’ published in Nepalese Heart Journal, Vol.6(1) 2009 pages 21-24 (DOI: https://doi.org/10.3126/njh.v6i1.18451) as the paper had already been published in the Journal of Research in Medical Sciences Vol.14(2) 2009 pages 123-127 http://jrms.mui.ac.ir/index.php/jrms/article/view/2353. This error is regretted, and we apologise for any inconvenience.